A new ergasilid copepod from lates perches in East Africa: morphology, phylogenetics, and genetic structure of Ergasilus ereimia sp. nov. - Vandenberg, Ferre; Kmentová, Nikol; Karanja, Hiram; Van Steenberge, Maarten; Vranken, Nathan; Vanhove, Maarten P. M.; Thys, Kelly J. M. (Frontiers in Veterinary Science, 2026)
Copepods are widely distributed across marine and freshwater environments and are often praised for their immense taxonomic and functional diversity. However, relatively little is known about parasitic copepods, particularly regarding their phylogenetic relationships. This study investigates the morphology and phylogenetic positioning of a proposed new species of parasitic copepods described as Ergasilus ereimia sp. nov. (Ergasilidae). The ectoparasitic female copepods (1,645 specimens) were obtained by performing parasitological screening of ethanol-preserved gills of lates perches from Lake Turkana (Kenya; 4 specimens of Lates niloticus, 6 specimens of Lates longispinis) and Lake Albert (Uganda; 5 specimens of L. niloticus) in East Africa. Light and confocal microscopy were used to conduct the morphological characterisation and to determine the spine-seta formula of the parasitic females. A differential diagnosis was conducted with all 18 other formally described species of Ergasilus from the African continent, which revealed E. ereimia sp. nov. to have a unique combination of morphological traits and a unique spine-seta formula. A phylogenetic tree was constructed using the concatenated partial sequences of the 18S and 28S ribosomal DNA (rDNA) genes. We hypothesised that E. ereimia sp. nov. would belong to the same clade as the other continental African ergasilids. This proved to be correct, and this taxon forms a well-supported sister clade to the other continental African species of Ergasilus with available sequence data. The intra- and interspecific model-corrected genetic distances were calculated based on the fragments of the 18S rDNA (average of 0.001 and 0.031 respectively) and 28S rDNA (average of 0.001 and 0.154 respectively) genetic markers, as well as on a fragment (1,122 bp) of the cytochrome c oxidase subunit I (COI) mitochondrial DNA (mtDNA) sequences (intraspecific average of 0.019), all of which further support the designation of a novel species of ergasilid copepods. A Neighbour Joining haplotype network based on the fragment of COI mtDNA showed ongoing diversification between the populations of E. ereimia sp. nov. from Lake Turkana and Lake Albert, in addition to the observed continuous intraspecific morphological variation in size and pigmentation.